Relationship between dental crowding and the oral hygiene index in 12-year-old school children - Albarracín-Pintado, Marcia P. (2021)
Objective: To determine whether there is a correlation between dental crowding and the oral hygiene index in 12-year-old schoolchildren in the Gil Ramírez Cuenca-Ecuador 2016 parish. Materials and methods: A correlational and retrospective study was conducted with a quantitative, descriptive approach. The total population studied belongs to a database that corresponds to a macro study carried out in 2016 under the name Epidemiological Map of Oral Health in 12-year-old Schoolchildren in Cuenca-Ecuador. When the database was accessed, a probability sampling was done and a sample of 188 cards was obtained. The statistical analyses were carried out in the SPSS program. Results: Male and female 12-year-olds in the Gil Ramírez parish did not present dental crowding, giving a 53,71%. When the variables were correlated, we obtained a mathematical value of Kendall's Tau-b of -0,128 and a p-value of 0,053 for the entire sample studied. Conclusions: It was determined that there was no significant correlation between dental crowding and the oral hygiene index in 12-year-old schoolchildren in the parish of Gil Ramírez Cuenca-Ecuador 2016.